Pengembangan Pembalut Pintar untuk Deteksi Dini Kondisi Hiperurisemia dan Hiperkolesterolemia - Dewi, Itut Septiana; Kuswandi, Bambang; Nugraha, Ari Satia (Pustaka Kesehatan, 2024)
Hyperuricemia and hypercholesterolemia’s cases are increasing. Noninvasive early detection method should be develope. Development of smart sanitary napkins based on paper chip biosensors using “Whatman” filter paper through screen printing and immobilized with pH 6 citrate buffer and iron (III)-actress- (1,10-phenanthroline) complex reagent for detection of uric acid and cholesterol oxidase enzymes and reagent 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid (ABTS)) for cholesterol detection. The analysis of the paper chip biosensor has a response time of 10 minutes for uric acid detection and 25 minutes for cholesterol detection. Uric acid linearity 2 - 20 mg / dL and cholesterol 50 - 500 mg / dL. The LOD and LOQ detection areas for uric acid were 0.322 mg / dL and 0.965 mg / dL, respectively, while the cholesterol detection areas were 8.740 mg / dL and 26.221 mg / dL, respectively. NaCl interference interfering with the detection of uric acid and cholesterol was 5.746% and 6.388%, respectively and creatinine interference interfering with the detection of uric acid and cholesterol was 5.868% and 5.583%, respectively. The precision for uric acid detection was 1.252% (RSD <3.7%) and cholesterol detection was 0.059% (RSD <2.7%). The accuracy (% recovery) for uric acid detection was 100.333% and for cholesterol, the detection was 100.016%. Smart bandages can be used to analyze the initial conditions of hyperuricemia and hypercholesterolemia.